Financial literacy: a barrier to home ownership for the young? - Gathergood, John; Weber, Jörg (Elsevier, 2017)
The decision to buy a home is one of the most important choices faced by a household. Most young households who purchase a home do so using a mortgage. But mortgages are complex financial instruments and this complexity may be a barrier to less sophisticated households becoming homeowners. Using survey data from a sample of English and Welsh households we measure household financial literacy related to mortgages, including concepts such as loan duration, interest compounding and amortization. We find that in the population mortgage financial literacy is generally low and among renters mortgage financial literacy is substantially worse than among homeowners. Econometric estimates show mortgage financial literacy predicts home ownership for younger, but not for older households. Financial literacy also affects the type of mortgage and leverage position of younger households. Young homeowners with poorer financial literacy take on larger mortgage debts and are more likely to use alternative mortgage products.